Anatomy of turner syndrome. Issue 5 (9th May 2016) - Granger, Andre; Zurada, Anna; Zurada‐Zielińska, Agnieszka; Gielecki, Jerzy; Loukas, Marios
Abstract : Turner syndrome (TS) is one of the most common sex chromosome abnormalities and results from total or partial monosomy of the X chromosome. It occurs in 1 in 2000 newborn girls and is also believed to be present in a larger proportion of conceptuses. There are various anatomic anomalies that have been associated with TS and the consequences of late recognition of these anomalies can be devastating. Aortic dilation and dissection occur at increased rates in TS patients and contribute to the decreased life expectancy of these patients. Such cases have prompted the need for early identification and continuous monitoring. Other anatomic variations increase morbidity in this population, and negatively impact the social and reproductive aspects of their lives. In this review, we summarize the cardiovascular, neurological, genitourinary, otolaryngolical, craniofacial, and skeletal defects associated with TS. To elucidate these morphological variations, novel illustrations have also been constructed. Clin. Anat. 29:638–642, 2016. © 2016 Wiley Periodicals, Inc.